KEKERASAN SIMBOLIK DALAM NOVEL INDONESIA - Sri Wahyuni; Haris Supratno; Kamidjan Kamidjan (Universitas Negeri Makassar, 2019)
Abstract: Symbolic Violence in Indonesian Novels. The general objective of this research is to find out the mechanism of symbolic violence, upper class habitus, and lower class habitus in the Indonesian novels. The approach used in this research is a qualitative approach. Data is collected using the documentation method. The results of the study of the mechanism of symbolic violence consisting of euphemisms in the form of compassion, giving, refusal are subtle. The censorship mechanism in the form of positive moral preservation in the form of honor and politeness. Upscale habitus in the form of hopes and lifestyles possessed by social groups above and class habitus under expectations and lifestyles owned by social groups below.